PENGARUH PERGANTIAN MANAJEMEN, UKURAN PERUSAHAAN, AUDIT FEE, DAN REPUTASI AUDIT TERHADAP AUDITOR SWITCHING - Naelah Sofiana; Murtanto Murtanto (STMIK Widuri Jakarta, 2024)
This study aims to examine the effect of management change, firm size, audit fees, and audit reputation on auditor switching which are used as the dependent variable. The data used is secondary data obtained from the financial reports of companies in the Industrial Sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. This sample consists of 40 companies selected using a technique known as purposive sampling. . Using multiple linear regression analysis, the relationship between variables is investigated in this study. This research was processed using SPSS Version 25. The results of this study, partially Management Change, company size, Audit Fee, and Audit Reputation have a positive effect on Auditor Switching. Simultaneously all variables have a positive and significant effect on profitability